LC–ESI–IT-MS/MS and MALDI-TOF Approach: Identification of Natural Polymers from Rhizophora mangle Barks and Determination of Their Analgesic and Anti-inflammatory Properties - de Souza Mesquita, Leonardo Mendes [UNESP]; Rodrigues, Caroline Fabri Bittencourt [UNESP]; da Rocha, Cláudia Quintino [UNESP]; Bianchim, Mayara Silveira [UNESP]; Rodrigues, Clenilson Martins; de Oliveira, Vanda Maria; Gaeta, Henrique Hessel [UNESP]; Belchor, Mariana Novo [UNESP]; Toyama, Marcos Hikari [UNESP]; Vilegas, Wagner [UNESP] (Springer Nature, 2019)
Abstract: We recognize the chemical composition of the acetonic extract of Rhizophora mangle barks (AERM) using mass spectrometry analysis [liquid chromatography (LC)–ESI–IT-MS/MS and matrix-assisted laser desorption/ionization-time of flight-MS (MALDI-TOF)]. Analgesic activity was evaluated by formalin and tail-flick experimental assays. Anti-inflammatory activity was performed by paw edema test induced by carrageenan and 48/80 compounds. The first series of experiments involved [LC]–FIA–IT-MS/MS with 11 separated catechins derivatives until degree of polymerization 3 (DP3). The spectra obtained by MALDI-TOF analysis of the AERM presented two homologous series: one based on polymers of m/z 288 Da increments (up to DP12) and another series based on polymers of m/z [288 + 162] Da increments (up to DP11). In addition to these series of flavan-3-ol, each DP had a subset of masses with a variation of − 16 Da (homologous series of afzelechins—m/z 873–3465 Da) and + 16 Da (homologous series of gallocatechins—m/z 905–3497 Da). A similar pattern with homologous series of gallocatechins and afzelechins could also be observed for a fifth and a sixth monohexoside series: glucogallocatechins (m/z 779–3371) and glucoafzelechins (m/z 747–3339). The intraperitoneal administration of different doses of AERM (50, 150 and 300 µg mL−1) have a morphine-like effect and intense anti-inflammatory activity. Graphical Abstract: [Figure not available: see fulltext.].
Keywords: Anti-inflammatory; Catechins; Mangroves; Morphine-like effect; Tannins